Transformation of Household Waste: Effective Ways to Convert It into Liquid Organic Fertilizer - Ahmad Rizal Fikri; Iqbal Imam Taufiq; Catelia Rifqi Lestari; Irma Juliana; Muhammad Azkiyak; Lathif Hanafir Rifqi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Household waste, although a significant environmental challenge, has the potential to be converted into valuable resources. This article discusses effective methods for transforming household waste into Liquid Organic Fertilizer (LOF), an environmentally friendly solution that improves soil quality and supports plant growth. By utilizing materials such as food scraps, fruit peels, and dry leaves, this process not only reduces the volume of waste sent to landfills but also benefits home gardening. The article outlines practical methods for producing LOF, including simple fermentation techniques, necessary equipment, and a step-by-step guide. It also discusses the ecological and economic benefits of using household waste as LOF and its impact on sustainability and waste management. With comprehensive and easy-to-follow information, this article aims to encourage individuals and communities to adopt these practices as part of their waste management and sustainable agriculture efforts.